15th Asia-Oceania Congress of Endocrinology (AOCE 2014) ORAL PRESENTATION ABSTRACTS - (AOCE 2014), Oral Presentors (Journal of the ASEAN Federation of Endocrine Societies, 2014)
The Organizing Committee of the 15th Asia Oceania Congress of Endocrinology (AOCE 2014) takes pride in submitting to the Journal of the ASEAN Federation of Endocrine Societies (JAFES) the research abstracts that were presented during the congress. The theme for the congress which was, “AOCE 2014 LEADER: Linking Endocrine and Diabetes Endeavors in the Region” captures exactly what the organizers intended. The congress itself was held last October 9-11, 2014 at the Radisson Blu Hotel, Cebu City Philippines but it was the hope of the organizing committee that even after the congress there will be further engagement and collaboration among the delegates of member and participating countries in both research and advocacy. There were a total of 98 research abstracts that were submitted, 17 of which were presented during the oral sessions and the remaining 77 as posters during the two and a half day congress. Publishing these abstracts in the JAFES is thus, very much welcomed and appreciated by the organizing committee. It is our hope that through this publication, we can inform the rest of the world not only about what researches were presented in the congress but what researches are happening in the member countries of the so-called Federation of Endocrine Societies in the Asia-Oceania Region. Likewise, we hope that the authors of these papers will be encouraged to submit their full paper for publication in the JAFES.